Influence of rough sea surface on sea surface reflections: deep towed high-resolution marine seismic case study - Egorov, A.; Glubokovskikh, Stanislav; Bona, Andrej; Pevzner, Roman; Gurevich, Boris; Tokarev, M. (2015)
Assumption of a flat sea surface with the reflection coefficient close to -1 has been known to be inadequate for many real life situations. A lot of attention has been paid to the topic of rough-sea problems in the recent time, largely because of the development of the deghosting algorithms, where the abovementioned assumption can be violated. In this paper, we present a comparison of rough sea surface reflection modeling results with ultra-high resolution field seismic data acquired with deep-towed sources and receivers. Such comparison is essential in establishing validity of the modeling approaches used in data processing, such as deghosting. Deep towed sources and receivers allow us to separate sea surface reflections from primary events to study them accurately.